Occurrence of Emphysema in Individuals With Williams-Beuren SyndromeTake-home Points - Uddalak Majumdar, MD; Theresa M. Kline, MLIS, AHIP; James K. Stoller, MD (CHEST Pulmonary)
Background: Williams-Beuren syndrome (WBS) is a multisystem genetic condition characterized by a submicroscopic deletion on the seventh chromosome (7q11.23), which usually includes the elastin gene. Research Question: Although the elastin deficiency in WBS can predispose individuals to emphysema, the prevalence of emphysema in WBS is unknown. This narrative review aims to address this gap by estimating the frequency of emphysema (or suggestive features thereof) in patients with WBS, with a special focus on concomitant alpha-1 antitrypsin deficiency. Study Design and Methods: Literature was reviewed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results: Of 419 studies identified by the search strategy, 19 eligible studies reported 393 adult patients with WBS. The criteria by which emphysema was assessed varied greatly among the relatively few reports addressing this issue. Chest CT evidence of emphysema was reported in three of 26 patients (11.5%). Physiologic evidence of airflow obstruction, although not definitive for emphysema (ie, with asthma not excluded), was present in as many as 38.6% of patients. Considering studies that reported multiorgan clinical manifestations of WBS, irrespective of whether chest CT imaging and/or pulmonary function testing was reported, the frequency of spirometric and imaging signs suggestive of emphysema was 4.3%. Emphysema was not reported in any of the 11 patients with concomitant PI∗MZ heterozygous alpha-1 antitrypsin deficiency. Interpretation: In the context that only few adults with WBS have been fully characterized regarding the occurrence of emphysema, confidently estimating the prevalence of emphysema is difficult. This review shows that the frequency of imaging and pulmonary function test abnormalities suggestive of emphysema seems relatively low in the context that the elastin deficiency of WBS clearly can predispose to emphysema, and that other manifestations of elastin deficiency are present early in life. Acknowledging the challenges of studying uncommon diseases or syndromes, further systematic study of adults with WBS is needed.